ASSESSING THE RAIN EROSIVITY AND RAIN DISTRIBUTION IN DIFFERENT AGRO-CLIMATOLOGICAL ZONES IN VENEZUELA - Deyanira Lobo Lujan; Donald Gabriels (Sociedade & Natureza)
Evaluating runoff and field soil losses by either empirical or physically based erosion models, requires an understanding and assessment of rainfall characteristics affecting the erosion (sub)processes.In spite of shortcomings and many criticisms on the worldwide use and applicability of RUSLE (Revised Soil Loss Equation), this empirical model still gains worldwide popularity for estimating erosion on a farmfield or micro-catchment scale.One of the limits of the model is the assessment of its climate factor in terms of rain energy and maximum storm intensity, both factors combined in the erosivity factor R, although they not easily available nor easily determinable. Therefore attempts are made to look for more easily determinable rain characteristics such as the monthly precipitation for evaluating the rain aggressiveness (or rain erosivity) on a monthly or yearly basis.As agro-climatological zones have typical rain distributions and rain concentrations, the Modified Fournier Index (MFI) and the Precipitation Concentration Index (PCI), both calculated from monthly precipitation values over a number of successive years, will be usedto characterize zones in Venezuela.Monthly rainfall data were collected for at least 10 successive years from nine stations in Venezuela: three stations in the Llanos Centrales, four stations in the Llanos Occidentales and two stations in the semiarid zone of Lara State.According to the available data sets, two different procedures were used to calculate (MFI):- In the first procedure the monthly rainfall amounts are averaged over a number of years.The (MFI) is then calculated from this averaged rainfall data set and reported as (MFI)1.- In the second procedure the (MFI) is calculated from the monthly rainfall amounts of each individual year and the (MFI) averaged over a number of years. Those long term average values are reported as (MFI)2.Temporal aspects of the rainfall distribution within a year was defined by the Precipitation Concentration Index (PCI) also based on monthly rainfall amounts and calculated following the two procedures as for determining the (MFI).From those stations of which R = EI30 was available an attempt was made to relate R to (MFI).